Proceedings. - ASEAN Science & Technology Week (Bicutan, Taguig, MM : ASEAN Committee on Science and Technology, Department of Science and Technology, 1989)
Contents. v.1. Opening ceremonies ... Country reports.--v.2. Biotechnology. Biodiversity.--v.3. Materials science and technology. New energy sources.--v.4. Information technology. Microelectronics. Laser technology. Optoelectronic and fibre optics. Superconductivity.
Keywords: Science -- Congresses; Technology -- Congresses